Corporealism and causality in the Ancient Stoa: an approach from a not-mathematical model - Bustos, Natacha (Estudios de Filosofía, 2014)
The present paper proposes to evaluate in which sense the conception of the corporeal held by Ancient Stoa doesn’t favour the spatial dimension. That is to say, we will analyse the Stoic argument according to which the place or the extension of a body isn’t determined by its position with regard to another body, but by its activity or power; more specifically, by its inner tension. Therefore, our initial objective will be to analyse the foundations that will allow us to account for the Stoic conception of a body from a biological principle and not from a mathematical model. And then, we will evaluate the definition in question in its articulations with the theory of causality and determinism.